PENGARUH VARIASI KECEPATAN FEEDING DAN KEDALAMAN PEMAKANAN END MILL TERHADAP TINGKAT KEKERASAN MATERIAL TEMBAGA - Aep Surahto; Fatimah Dian Ekawati; Ellysa Kusuma Laksanawati (Universitas Muhammadiyah Tangerang, 2022)
Determination of milling parameters using a variation of feeding speed and appropriate infeed depth is very important to obtain the desired surface roughness. The purpose of this study was to determine the fedding speed and infeed depth which resulted in the lowest and highest quality of roughness in the milling process. Parameters of variation of feeding speed used are 24 mm / min, 42 mm / min, 74 mm / min and meanwhile for the feeding depth is 0.1 mm, 0.3 mm, 0.5 mm. The results of the SJ-210 mitutoyo SJ-210 surface roughness tester were found, the surface roughness value from the infeeding depth of 0.1 mm was 1.222 and the average magnification value was 1.133 , the result of the infeeding depth was 0.3 mm. The roughness was 1.863 and the average magnitude was 1.598 , and the result of the infeeding depth of 0.5 mm the roughness value was 3.915 and the average magnitude was 3.566 . So this results in a better milling process and efficiency in terms of workmanship and results, resulting in the best surface roughness value on N7 with an average surface roughness value of 1.540 .